Indicators of rapid cognitive decline in amnestic mild cognitive impairment: The role of plasma biomarkers using magnetically labeled immunoassays. (October 2020) - Tsai, Chia-Lin; Liang, Chih-Sung; Yang, Chun-Pai; Lee, Jiunn-Tay; Ho, Tsung-Han; Su, Ming-Wei; Lin, Guan-Yu; Lin, Yu-Kai; Chu, Hsuan-Te; Hsu, Yu-Wei; Yang, Fu-Chi
Abstract: Plasma levels of biomarkers change with the progression of Alzheimer's disease (AD), which involves the accumulation of pathological amyloid β (Aβ) and Tau protein tangles. However, few studies have investigated the association between plasma biomarkers and rapid cognitive decline in patients with amnestic mild cognitive impairment (aMCI) and AD. A total of 10 healthy controls, 24 patients with aMCI, and 19 patients with AD were enrolled. All participants underwent twice Mini-Mental State Examination (MMSE), with a mean 1.2 year interval. Immunomagnetic reduction was utilized to evaluate levels of plasma biomarkers, including amyloid β 1–40 (Aβ1-40 ), Aβ1-42, total Tau protein, phosphorylated Tau protein (Threonine 181), and α-synuclein (α-Syn). The correlations between plasma levels of biomarkers and MMSE change were examined. Our analysis reveals that current higher plasma levels of Aβ1-42 and α-Syn with the cut-off value of plasma Aβ1-42 >17.26 pg/mL and α-Syn >105 fg/mL had a moderate-to-high discriminatory capacity (area under the curve >0.70) for identifying cognitive deterioration in patients with aMCI. Our results thus suggest that plasma levels of Aβ1-42 and α-Syn may be considered as useful markers to assess the severity of global cognitive decline in patients with aMCI.